Human Herpesviruses 6, 7 and 8 in Solid Organ Transplant Recipients. Issue 3 (24th January 2013) - Razonable, R. R.
<x xml:space="preserve">Abstract</x> Human herpesviruses (HHV) 6 and 7 are ubiquitous infections that reactivate commonly in transplant recipients. However, clinical diseases due to these viruses are reported only in 1% of solid organ transplant recipients. Fever, rash and bone marrow suppression are the most common manifestations, but symptoms of tissue invasive disease may be observed. Treatment of HHV‐6 and HHV‐7 disease includes antiviral therapy and cautious reduction in immunosuppression. HHV‐8 is an oncogenic gamma‐herpesvirus that causes Kaposi's sarcoma, Castleman's disease and primary effusion lymphomas in transplant recipients. Nonmalignant diseases such as bone marrow suppression and multiorgan failure have also been associated with HHV‐8. Reduction in immunosuppression is the first line treatment of HHV‐8 infection. Other alternatives for treatment, especially for HHV‐8 diseases not responsive to immuno‐minimization strategies, are surgery and chemotherapy. Sirolimus has been shown to be a beneficial component for the treatment of Kaposi's sarcoma and the role of antivirals for HHV‐8 infection is being investigated.